Music on stage. The Spanish musical diplomacy in the United States of America (1939-1970) - Lillo Espada, Samuel (Cuadernos de Historia Contemporánea, 2020)
This article analyses Spanish music in the United States of America, understood as an element of soft power used by the governments in their international dimension. Since the Second World War, the relationships between Spain and United States have suffered numerous changes which have been reflected in the musical diplomacy developed by the both. The government of Franco promoted the regional dances to improve the perception of Spain in American society and delete the negative image from the war. On the other hand, the American government tried to change the Spanish anti-Americanism, developed in its society during the post-war years, through jazz.
Keywords: Musical diplomacy; soft power; flamenco; jazz; Francoism; Spain; United States